Aging‐induced aberrant RAGE/PPARα axis promotes hepatic steatosis via dysfunctional mitochondrial β oxidation. Issue 10 (16th September 2020) - Wan, Jian; Wu, Xiangsong; Chen, Hanbei; Xia, Xinyi; Song, Xi; Chen, Song; Lu, Xinyuan; Jin, Jie; Su, Qing; Cai, Dongsheng; Liu, Bin; Li, Bo
Abstract: Non‐alcoholic fatty liver disease (NAFLD), characterized by an increase in hepatic triglyceride (TG) content, is the most common liver disease worldwide. Aging has been shown to increase susceptibility to NAFLD; however, the underlying molecular mechanism remains poorly understood. In the present study, we examined hepatic TG content and gene expression profiles in body weight‐matched young (3 months old), middle‐aged (10 months old), and old (20 months old) C57BL/6 mice and found that TGs were markedly accumulated while mitochondrial β‐oxidation‐related genes, including PPARα, were downregulated in the liver of old mice. In addition, advanced glycation end product receptor (RAGE), a key regulator of glucose metabolism, was upregulated in the old mice. Mechanistically, suppression of RAGE upregulated PPARα and its downstream target genes, which in turn led to reduced TG retention. Finally, we found that hepatic RAGE expression was increased in aging patients, a finding that correlated with decreased PPARα levels. Taken together, our findings demonstrate that the upregulation of RAGE may play a critical role in aging‐associated liver steatosis. Abstract : We propose that aging induces RAGE upregulation, which inhibits PPARα signaling and suppresses mitochondria‐related fatty acid β‐oxidation, eventually leading to excessive FFA production and then hepatic steatosis.